Hubungan E-Wom, Consumer Ethnocentrism, Brand Equity dan Purchase Intention pada Sepatu Merek Indonesia - Nicholas Skiefer; Caroline Suwandi; Fathony Rahman; Antonius W. Sumarlin (Universitas Prasetiya Mulya, 2023)
Amidst the flood of imported goods from China over the past 20 years, the Indonesian government launched the national movement called Bangga Buatan Indonesia (Gernas BBI). This phenomenon provides an opportunity to generate consumer ethnocentrism and brand equity to help Indonesian SMEs improve their loyalty and competitiveness towards their brands. This study builds on previous research on the relationship between e-wom, consumer ethnocentrism, and brand equity, by replacing brand equity to make it more relevant and adding purchase intention to determine which factors can drive purchasing interest and what motivates that interest. To make this study more relevant to the current situation, the researchers also adopted a theoretical study. SEM analysis was conducted with 320 respondents using non-probability techniques. The results showed that positive e-wom has a greater influence on the purchase intention of domestic shoe brands. To compete against foreign shoe brands, owners of domestic shoe brands must rely more on positive e-wom than consumer ethnocentrism.